Ultrasound Guided Peripheral Nerve Block for Trigeminal Neuralgia: A Case Report - Bambang Sulistyo (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Trigeminal neuralgia (TN), sometimes referred to as tic doloureaux or Fothergill disease, is a facial nerve disorder that is widely recognized as one of the most excruciating human ailments. It is characterized by sudden, severe, and recurrent episodes of facial pain that can significantly impair a patient’s quality of life. Oral medications are commonly used as first-line therapy; however, they fail to provide long-term relief in approximately half of patients with trigeminal neuralgia. This condition often leads to repeated clinical visits and the need for alternative therapeutic approaches. A 26-year-old woman presented with complaints of severe, intermittent, and sharp pain localized to her left cheek, consistent with the clinical features of trigeminal neuralgia. Several minimally invasive and surgical treatment options are available for managing this condition, including radiofrequency procedures and microvascular decompression. However, these approaches still carry certain risks and may not be acceptable to all patients. Due to its lower risk profile, ultrasound-guided peripheral nerve block can serve as an effective and safer alternative treatment, particularly for patients who refuse or are not suitable candidates for invasive or surgical interventions.